2011
DOI: 10.1186/cc10189
|View full text |Cite
|
Sign up to set email alerts
|

Positive end-expiratory pressure can increase brain tissue oxygen pressure in hypoxemic severe traumatic brain injury patients

Abstract: Introduction Noninvasive ventilation is a safe and eff ective method to treat acute respiratory failure, minimizing the respiratory workload and oxygenation. Few studies compare the effi cacy of diff erent types of noninvasive ventilation interfaces and their adaptation. Objective To identify the most frequently noninvasive ventilation interfaces used and eventual problems related to their adaptation in critically ill patients. Methods We conducted an observational study, with patients older than 18 years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…There are several limitations in our study that deserve to be mentioned. First, the sample size is small, despite similar to previous physiological studies exploring the effect of PEEP on lung recruitment (Mascia et al, 2005;Nemer et al, 2011;Mauri et al, 2016Mauri et al, , 2020.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…There are several limitations in our study that deserve to be mentioned. First, the sample size is small, despite similar to previous physiological studies exploring the effect of PEEP on lung recruitment (Mascia et al, 2005;Nemer et al, 2011;Mauri et al, 2016Mauri et al, , 2020.…”
Section: Discussionmentioning
confidence: 98%
“…An a priori sample size calculation was not feasible due to the lack of data on quantitative CT analysis in brain-injured patients, but our sample size was similar to previous physiologic studies regarding PEEP augmentation in ARDS or brain-injured patients (Mascia et al, 2005;Nemer et al, 2011;Mauri et al, 2016Mauri et al, , 2020. Data are reported as median (interquartile range, IQR), if not otherwise specified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In ARDS, the alveoli collapse and become fluid filled. Furthermore, researchers have found that PEEP can positively influence the brain tissue oxygen pressure in patients with brain injury and ALI (Nemer et al, 2011). However, PEEP also increases intrathoracic pressure with the potential to increase resistance to passive cerebral venous blood flow and cerebral spinal fluid outflow.…”
Section: Peepmentioning
confidence: 99%